Pengendalian Kebijakan Larangan Impor Pakaian Bekas di Kota Surabaya - Ulfatillah Salmi; Ertien Rining Nawangsari (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
This study aims to analyzed the policy control of Minister of Trade No. 40 of 2022 by Tanjung Perak Customs in Surabaya City. Despite the policy that used clothing is prohibited from being imported, the phenomenon of thrifting and circulation of imported used clothing is still found, including in Pasar Pagi Tugu Pahlawan Surabaya. This research uses a qualitative method with data collection through observation, interviews, and documentation of Tanjung Perak Customs employees and imported used clothing traders. Data analysis used the Miles and Huberman interactive model, and triangulation for data validity. The results showed that policy control by Tanjung Perak Customs was carried out through three dimensions according to Riant Nugroho's theory, namely: (1) Monitoring, has reflected early detection efforts for the entry of imported used clothing through document and physical checks in the Customs area; (2) Evaluation, comparing the results of supervision that are close to policy objectives, system improvements, and increased enforcement that reflects the intensity of supervision; and (3) Rewards carried out in the form of confiscation and destruction of imported used clothing as a form of administrative sanctions for violations, as well as news in the mass media and customs classes to overcome challenges from the importer side such as the principle of “ignorance”. The conclusion is that although policy control in the Customs area has been implemented, it is necessary to strengthen coordination between institutions in the field and the strong economic motives of imported used clothing traders cause the policy to not be fully implemented properly in the field.